Aptamer Sequence Optimization and Its Application in Food Safety Analysis - Xinna Qin; Lina Zhao; Yang Zhang; Jiyong Shi; Haroon Elrasheid Tahir; Xuechao Xu; Kaiyi Zheng; Xiaobo Zou (Foods)
Aptamers are single-stranded DNA or RNA oligonucleotides screened by systematic evolution of ligands by exponential enrichment (SELEX) methods, which are widely used in food analysis. Aptamers have the advantages of low molecular weight, ease of preparation, simplicity of chemical modification, and structural stability. Aptamers generated by SELEX are typically 80–100 bases in length, and the affinity of the aptamer can be improved by sequence optimization. Methods of aptamer optimization commonly include truncation, mutation, and chemical modification, and molecular docking, molecular dynamics, circular dichroism, and isothermal titration to assess often the binding performance of the aptamer to the target. Optimized aptamers usually enhance the affinity of the aptamer for the target and increase its sensitivity in the detection of pesticides, heavy metals, fungal toxins, pathogenic bacteria, and other objects. This paper focuses on truncation, mutation, chemical modification, the introduction of rare nucleotides, and computer-aided design. It provides an overview of non-immobilized optimization metrics.